PENGARUH STORE ATMOSPHERE, PROMOTION, DAN MERCHANDISING TERHADAP IMPULSE BUYING PADA PELANGGAN CLANDY’S CABANG BULUH INDAH DENPASAR - I Made Surya Prayoga (JUIMA : JURNAL ILMU MANAJEMEN, 2021)
Consumer emotional feelings when shopping often lead to impulsive purchases. Impulse buying also occurs when consumers experience an emotional urge to buy a product, without wise consideration of why and for what reasons to buy a product. The behavior of consumers who sometimes shop unplanned must be seen as an opportunity that must be responded to with a serious strategy. Some marketing strategies that can be used, especially retail marketing strategies, are store atmosphere, promotion, and merchandising. This research was conducted on customers of Buluh Indah branch clandys located in the city of Denpasar. The sampling technique used a purposive sampling method using 114 respondents. The data analysis technique used to test the deep hypothesis is multiple linear regression analysis with analysis tools using the SPSS version 22 For Windows program. The results showed that store atmosphere, promotion, and merchandising had a positive and significant effect on impulse buying